Pentylenetetrazol-induced seizures and brain neuroinflammation markers under conditions of pitolisant and pioglitazone use - Yehorenko, O.; Pervak, M. (Journal of Education, Health and Sport, 2025)
The purpose of the study was to investigate the dynamics of seizure activity and markers of neuroinflammation in kindled rats under conditions of individual and combined use of pitolisant and pioglitazone. Under conditions of acute observation in rats kindled with pentylenetetrazol, repeated administration (35.0 mg/kg, i.p.) of the behavioral, electrographic seizure manifestations, the density of microvessels, and the level of HIF-1α in brain structures have been investigated. The data obtained showed that pitolisant use in previously ineffective dosage (5,0 mg/kg, i.p.) but against the background of the administration of pioglitazone (50,0 mg/kg, i.p.) was accompanied by the anticonvulsant effect, which was expressed as prevention of generalized tonic-clonic seizures as well as in reduction of seizure severity and triple shortage of the ictal discharges duration in brain frontal cortex. Also, combined administration of pitolisant (5,0 mg/kg, i.p.) and (50,0 mg/kg, i.p.) prevented kindling-induced angiogenesis in the frontal cortex by 55,2% and the level of HIF-1α in the hippocampal gyrus dentatus by 38,6%. Thus, complex antiepileptic effects significantly exceeded those observed after separate drug administration have been described. These data support the synergistic antiepileptic action of the investigated compounds, favoring the rationality of exploring a combination of modulators of the histaminergic system with PPAR-γ agonists as antiseizure therapy.